Conversion of Convensitonal Cooperatives to Improve the Islamic Economic - Sabri; Okfi Resti; nasfi; Suhatman (Adpebi International Journal of Multidisciplinary Sciences, 2023)
Purpose - This study aims to determine the influence of perceptions in terms of Islamic economics of converting cooperatives into Islamic cooperatives. Methodology/approach – This research is a quantitative descriptive type, a sample of 120 members and management of the Cooperative, research from August to October 2022, data were analyzed using validity and reliability tests and linear regression techniques. It Research findings, the results of this test obtained a tcount of 3.960 and a ttable of 1.981. The value of tcount > ttable means that there is an influence between the variables X and Y. The perceptions of members and management of cooperatives that convert Islamic cooperatives from an Islamic economic perspective have a significant effect on becoming Islamic cooperatives. Novelty/value –  There are many factors that fail to convert sharia and do not develop sharia cooperatives. The novelty of this study examines the perceptions of Islamic economics in Muslim-majority areas.